A Shear Deformation Theory of Beams with Bisymmetrical Cross-Sections Based on the Zhuravsky Shear Stress Formula - MAGNUCKI, Krzysztof; LEWIŃSKI, Jerzy; MAGNUCKA-BLANDZI, Ewa (Engineering Transactions, 2020)
This paper is devoted to simply supported beams with bisymmetrical cross-sections under a generalized load. Based on the Zhuravsky shear stress formula, the shear deformation theory of a planar beam cross-section is formulated. The deflections and the shear stresses of example beams are determined. Moreover, the numerical-FEM computations of these beams are carried out. The results of the research are shown in figures and tables.